GAMBARAN UMUM PEMASARAN PRODUK DAN JASA PERBANKAN SYARIAH - Muhammad Isa (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2016)
Marketing is one of the important function besides financial, production, and human resources management. Islamic Bank’s goal not only gets high profit but also community services. Marketing is the main tool to reach its goal. Services marketing, like banking, is different with goods marketing. Service marketing based on 7 elements of marketing mix. They are product, price, place, promotion, people, process, and physical evidence.